Expenditure of Low-Income Households on Energy : Evidence from Africa and Asia - Bacon, Robert; Bhattacharya, Soma; Kojima, Masami (World Bank, Washington, DC, 2014)
Patterns of household energy use and expenditure have been the subject of a large number of studies. Household expenditures on energy-particularly, how much the poor spend-have policy implications for several reasons. First, policies to mitigate or cope with energy price shocks are increasingly focusing on targeted support to low-income households as a way of limiting the fiscal cost of such policies while offering protection to the most vulnerable members of society. Second, for governments looking to reform energy price subsidies, the effects on household welfare- especially effects on poor households-of price increases resulting from subsidy reduction/removal is an important policy consideration. But subsidies for liquid fuels targeting the poor are difficult to design and implement effectively, because liquid fuels tend to be used more by the rich than by the poor, and are also easy to transport (and hence to divert to non-poor users). For this reason, there is a growing recognition of the need to move away from price subsidies for liquid fuels to alternative forms of targeted assistance to compensate the poor for the adverse effects of higher fuel prices. Third, in areas where many households have not yet begun using modern commercial energy regularly, the amount they can afford to pay for such energy services is a relevant question. Quantifying expenditures on different types of energy at varying income levels provides a basis for addressing these questions. The paper also examines expenditures on motorized passenger transport and food, two items for which the price of oil is an important component of their cost structure and which are consequential in the budget of poor households.